Molten Salt Storage for Power Generation. Issue 4 (11th February 2021) - Bauer, Thomas; Odenthal, Christian; Bonk, Alexander
Abstract: Storage of electrical energy is a key technology for a future climate‐neutral energy supply with volatile photovoltaic and wind generation. Besides the well‐known technologies of pumped hydro, power‐to‐gas‐to‐power and batteries, the contribution of thermal energy storage is rather unknown. At the end of 2019 the worldwide power generation capacity from molten salt storage in concentrating solar power (CSP) plants was 21 GWhel . This article gives an overview of molten salt storage in CSP and new potential fields for decarbonization such as industrial processes, conventional power plants and electrical energy storage. Abstract : An overview of molten salt energy storage in commercial concentrating solar power plants as well as new fields for its application is given. With regard to the latter, energy‐intensive industrial processes, conventional power plants, and bulk electrical storage sytems are discussed.